To Study the Effect of Waste Glass Powder and Zirconium Phosphate on the Properties of Intumescent Fire-Retardant Coating - Abdull Hadi, Mohd Ameerul Haziq (IRC, 2020)
Char is rather weak in mechanical strength, or if it cannot adhere to substrate, causing ineffectiveness of intumescent coating systems and make it unable to insulate a material. This study seeks to understand how adding waste glass powder and Zirconium Phosphate can strengthen the char in an epoxy-based intumescent fire-retardant coating and its effect on the based and fillers on thermal performance. The 5cm x 5cm coated samples was placed inside the furnace test machine to undergo furnace test, at 600°C by rate 20oC/min for one hour to determine the physical properties of the char produced. The samples were then immersed in the seawater for 15 days to undergo immersion test to determine the effect of natural environment towards the thickness and the weight of the samples. Finally, the thermal performance of the coating was examined through a fire testing process wherein the coated samples of 10cm x 10cm were burned up to a high temperature and backside temperature of the substrates was recorded using a Data Logger.